Perkembangan Transaksi E-Commerce Berdasarkan pada Metode Pembayaran, Kategori Produk dan Kelompok Usia di Kalimantan Selatan - Siti Mahfuzah; Ika Chandriyanti (PPJP Universitas Lambung Mangkurat, 2022)
This research was conducted to analyze: The development of e-commerce transactions based on payment methods, product categories, and age groups in South Kalimantan.The number of transactions in this study was payment methods, product categories, and age groups in South Kalimantan. The number of e-commerce transactions starts from January 2018 - to May 2020. This research uses qualitative descriptive analysis techniques.This study provides results that the development of e-commerce transactions has increased from 2018 to 2020